SEROPOSITIVE BRUCELLOSIS IN BEEF CATTLE IN THE FIRST SEMESTER AT PANTOLOAN ANIMAL INSTALLATION - Rohmah, Sri Hidayatul (Universitas Airlangga, 2023)
Brucellosis is an infectious disease caused by bacteria of the genus Brucella and classified as a zoonotic disease. Brucellosis is usually asymptomatic in infected female animals, but it can cause placentitis, which leads to abortion in the fifth to ninth months of pregnancy in pregnant animals. Brucella infection is lifelong in animals, and Brucella bacteria can be found in the blood, urine, milk, and sperm. To prevent the spread of brucellosis in beef cattle that will be trafficked through the Pantoloan animal quarantine installation. From January to June, blood serum of male beef cattle was collected at the Pantoloan Animal Quarantine Installation, Palu Agricultural Quarantine. The Rose Bengal Test method was used on up to 7.046 serum samples. In the first semester of 2018, the positive incidence of blood serum testing for beef cattle using the Rose Bengal Test (RBT) method at ten beef cattle traffic frequencies revealed seropositive brucellosis in 38 out of 7,046 samples tested. Beef cattle were sourced from the Central Sulawesi, Gorontalo, and South Sulawesi provinces. Blood serum samples from Central Sulawesi showed the highest positive incidence. Based on the prevalence of seropositive brucellosis based on RBT in beef cattle transported through the Pantoloan animal quarantine installation, several cattle breeding areas should be monitored during subsequent traffic, and public awareness should be raised to prevent the spread of brucellosis.